Profil Mineral Kalium (K) Dan Kobalt (Co) pada Serum Sapi Bali yang Dipelihara Di Lahan Perkebunan - Dwipartha, Putu Satya; Suarsana, I Nyoman; Suwiti, Ni Ketut (Buletin Veteriner Udayana; Vol. 6 No. 2 Agustus 2014, 2014)
This study aimed to determine the profile of the mineral potassium (K) and Cobalt (Co) on 15 bali cattle reared on the farm in the Payangan Village,  District of Gianyar, Bali Province. The method used to measure the mineral content of the blood serum with a wet ashing method using HNO 3 and H 2 SO 4 .  Data were analyzed using qualitative descriptive analysis. The result show that the mean of 24.8436 ±0.02591 mg / l potassium and cobalt at 1.8026 ±0.01709 mg/l for Cobalt. This data is higher than normal levels of minerals in cattle.
Keywords: Bali Cattle, Plantation, Potassium, Cobalt